Analysis of electrical characteristics of ceramics on the basis of ZnOBi[2]O[3], obtained by spark plasma sintering; Gas Discharge Plasmas and Their Applications (GDP 2019) - Sivkov A. A. Aleksandr Anatolyevich; Ivashutenko A. S. Alexander Sergeevich; Rakhmatullin I. A. Ilyas Aminovich; Shanenkova Yu. L. Yuliya Leonidovna; Tsimmerman (Cimmerman) A. I. Aleksandr Igorevich (2019, 2019)
Заглавие с титульного экрана